CRYSTAL: a multi-agent AI system for automated mapping of materials' crystal structures. (June 2019) - Gomes, Carla P.; Bai, Junwen; Xue, Yexiang; Björck, Johan; Rappazzo, Brendan; Ament, Sebastian; Bernstein, Richard; Kong, Shufeng; Suram, Santosh K.; van Dover, R. Bruce; Gregoire, John M.
Abstract: Abstract : We introduce CRYSTAL, a multi-agent AI system for crystal-structure phase mapping. CRYSTAL is the first system that can automatically generate a portfolio of physically meaningful phase diagrams for expert-user exploration and selection. CRYSTAL outperforms previous methods to solve the example Pd-Rh-Ta phase diagram, enabling the discovery of a mixed-intermetallic methanol oxidation electrocatalyst. The integration of multiple data-knowledge sources and learning and reasoning algorithms, combined with the exploitation of problem decompositions, relaxations, and parallelism, empowers AI to supersede human scientific data interpretation capabilities and enable otherwise inaccessible scientific discovery in materials science and beyond.